Complete dental rehabilitation utilizing removable partial dentures and monolithic zirconia crowns (case report) - Hagar Ibrahim; Marwan Aggag (Advances in Medical, Pharmaceutical and Dental Research, 2024)
Bilateral edentulous areas are a common clinical presentation, and in most of those cases, implant repair may not be possible. As a result, the conventional metallic partial denture is still in use. As our awareness of appearance has grown in our daily life , esthetics became a crucial component of dentistry. consequently, patients ask for aesthetic restorations that also maintain functionality. Zirconia is a widely used material for both functional and aesthetic demands. It has been demonstrated that zirconia can endure occlusal and functional stresses without neglecting the aesthetic appearance that is expected of a tooth-colored restoration. which is why using it as surveyed crowns to support partial dentures is optimal.   Objectives: The goal of this case study is to demonstrate a method for restoring a partially edentulous patient through the use of a metallic partial denture held up by surveyed zirconia crowns using CAD-CAM technology.   Received: 14 July 2024 Accepted: 01 September 2024 Published: 19 September 2024